Effects of dietary natural vitamin E supplementation on laying performance, egg quality, serum biochemical indices, tocopherol deposition and antioxidant capacity of laying hens - Haoran Zhao; Yueping Chen; Shiqi Wang; Chao Wen; Yanmin Zhou (Italian Journal of Animal Science, 2021)
This study was to evaluate the effects of dietary natural vitamin E supplementation on laying performance, egg quality, serum biochemical indices, tocopherol deposition and antioxidant capacity of laying hens. A total of 360 46-week-old Hyline Brown hens were randomly assigned into five treatments consisting of six replicates with 12 hens each for a 9-week feeding trial. Birds were fed a basal diet supplemented with 0, 25, 50, 75, and 100 mg/kg natural vitamin E, respectively. Natural vitamin E linearly increased egg production and egg mass (p < .05), linearly decreased feed conversion ratio (p < .05) and linearly and quadratically increased feed intake (p < .05). The total tocopherol concentration in liver and yolk increased quadratically and linearly with increasing levels of natural vitamin E, respectively (p < .05). A linear decrease in content of serum low-density lipoprotein cholesterol was observed (p < .05). Supplementation of natural vitamin E linearly decreased serum malondialdehyde (MDA) level, linearly increased hepatic total antioxidant capacity (T-AOC) and catalase (CAT) activities, quadratically increased serum CAT activity and linearly and quadratically decreased hepatic MDA accumulation (p < .05). In conclusion, natural vitamin E can enhance laying performance, regulate serum cholesterol concentration, promote tocopherol deposition and improve antioxidant capacity, and dietary supplementation at a dosage of 100 mg/kg was recommended.Highlights Dietary supplementations of natural vitamin E significantly improved laying performance of hens. Dietary supplementations of natural vitamin E significantly increased tocopherol concentration of liver and yolk. Dietary supplementations of natural vitamin E significantly improved antioxidant capacity of hens.